2013
DOI: 10.1017/s0021900200013188
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Distributions of Processes Related to Fractional Brownian Motion

Abstract: Conditional distributions for affine Markov processes are at the core of present (defaultable) bond pricing. There is, however, evidence that Markov processes may not be realistic models for short rates. Fractional Brownian motion (FBM) can be introduced by an integral representation with respect to standard Brownian motion. Using a simple prediction formula for the conditional expectation of an FBM and its Gaussianity, we derive the conditional distributions of FBM and related processes. We derive conditional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…Such processes appear in finance, hydrology, telecommunication, turbulence and image processing. In particular, various financial applications of the fractional Vasicek model (1.2) can be found in the articles [3][4][5][6][7][8][9]21]. The goal of the paper is to construct maximum likelihood estimators (MLEs) for the unknown parameters α and β and to establish their consistency and asymptotic normality.…”
Section: Introductionmentioning
confidence: 99%
“…Such processes appear in finance, hydrology, telecommunication, turbulence and image processing. In particular, various financial applications of the fractional Vasicek model (1.2) can be found in the articles [3][4][5][6][7][8][9]21]. The goal of the paper is to construct maximum likelihood estimators (MLEs) for the unknown parameters α and β and to establish their consistency and asymptotic normality.…”
Section: Introductionmentioning
confidence: 99%
“…Grippenberg and Norros [8] provided a technical and difficult approach to calculate the conditional mean of fBm. Fink et al [5] also addressed this problem when studying the price of a zero-coupon bond in a fractional bond market. Since fBm is generally not a Markov process, both authors restricted themselves to calculate conditional expectations given the current value of B H t , and not given the whole path of B H t preceding t.…”
Section: Introductionmentioning
confidence: 99%
“… ddλ(t)=λdλ(t)dt+Md(dt),tR. Based on the earlier work of Zähle () and Buchmann & Klüppelberg (), Fink & Klüppelberg () showed that under some conditions on coefficient functions of a general SDE, dX(t)=μ(X(t))dt+σ(X(t))Md(dt),tR, pathwise solutions can be obtained in the form X(t)=f()scriptℳdλ(t),tdouble-struckR, where f is an invertible function. Using the well‐known Fourier techniques, like in Theorem 3.8 of Fink et al (), we can straightforwardly calculate the conditional characteristic function of such pathwise solutions under assumption of existing suitable exponential moments of scriptℳdλ via double-struckE[]|eiuf()scriptℳdλ(t)scriptFsscriptℳdλ=double-struckE[]|eiuf()scriptℳdλ(t)scriptFsMd1em=double-struckR()double-struckE[]|e(…”
Section: Applications To Fractional Time Series Models and Stochasticmentioning
confidence: 99%